Adding clinical markers of more severe form of intermediate-high risk pulmonary embolism improves risk stratification and possibly identifies candidates for fibrinolytic therapy. (2nd May 2022) - Radovanovic, N; Radosavljevic-Radovanovic, M; Prodanovic, M; Savic Spasic, L; Lojovic, N; Kecman, E; Djekic, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The authors of PEITHO study recently proposed 3 changes for future trials, in order to identify a higher-risk population among patients with intermediate-high risk PE, as potential candidates for thrombolysis: 1. longer early follow-up (30 days); 2. triple adverse composite endpoint (TACE): death, non-fatal hemodynamic collapse, or non-fatal recurrent PE; and 3. inclusion of 1 or 2 clinical indicators of PE severity, namely SBP ⩽110 mmHg or respiratory rate (RR) >20 breaths/min, in addition to established clinical score, imaging and biochemical criteria. Purposes: a.) to investigate whether these clinical markers identify pts at higher risk for 30-days TACE in our study population; b.) to define the best cut-off values of these markers, as well as other significant predictors in our population; and c.) to evaluate the effect of fibrinolytic therapy (FT) compared to heparin in this, higher risk group of pts. Methods: From the institutional PE registry, 148 consecutive pts with intermediate-high risk PE and 30 days follow-up were identified and divided into 3 groups: group 1 – pts with SBP ⩽110 mmHg; group 2 – pts with RR >20 breaths/min and group 3 – pts without any of these markers. The primary endpoint was as previously defined and the safety outcomes were updated TIMI non-CABG related bleeding. The outcome of these 3 groups of pts was compared separately, in the non-FT (heparin) group and in the FT group. For cut-off values determination, ROC analysis was used. The association of FT and 30-days outcome in the highest risk group of pts was analyzed by propensity score (PS)-adjusted Cox regression analysis. Results: Pts in group 1 and 2, treated with heparin, had significantly higher incidence of TACE compared to patients in group 3 (p=0.033 and p=0.004, respectively). In contrast, there was no difference in TACE between 3 groups, if they were treated with FT. Also, pts in group 2 were at 4.7 times higher risk for TACE compared to group 3, if treated with heparin. The optimal cut-off value of RR in our study was 24 breaths/min. The most important predictor of TACE in our study was shock index (OR (95%CI); 4.58 (1.38-15.25)), with a cut-off value of 0, 82 (sens. 95%, spec. 59%). When we tested the effect of FT (adjusted to PS) on TACE in patients with RR > 24/min and shock index > 0.82, we obtained significant reduction of TACE compared to pts treated with heparin (OR (95%CI); 0.30 (0.01–0.56); p = 0.027). The incidence of bleeding in our study was higher in pts treated with FT (12.9% vs 6% in the non-FT group; p=0.04), but not the major or fatal ones. Conclusion: Patients with SBP ≤110 mmHg or RR >20 breaths/min do have worse prognosis, when treated with heparin, compared to those without these clinical markers. Still, in our study, the best cut-off value of RR was higher – 24 breaths/min, and the best predictor of TACE was shock index > 0.82. These pts may benefit from fibrinolytic therapy, without an increase of fatal bleeding.